Pharmacognostic and Phytochemical Investigation of Kigelia africana Lam Benth Fruits - Bhramaramba, R (International Journal of Pharmaceutical & Biological Archive, 2013)
Pharmacognostic and Phytochemical Investigation of Kigelia africana Lam Benth Fruits